2013
DOI: 10.1515/jbcpp-2012-0062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gallic acid on oxidative stress-linked streptozotocin-induced pancreatic dysfunction in diabetic rats

Abstract: The direct influence and consequent restoration of altered biochemical conditions in the pancreatic tissue of diabetic animal models by GA makes it a promising antidiabetic candidate especially in pancreatic cell regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…In the present study, the amount of LPO product, MDA was higher in diabetic rats' pancreas as compared no non-diabetic rats indicating of high levels of oxidative stress due to intensified free-radical formation 53 . Our findings were in agreement with Kade et al 54 who reported that high amount of LPO product was observed in diabetic rats' pancreas. C. borivilianum root extract administration to diabetic rats lowered the LPO product, indicating that this plant extract could prevent elevation of oxidative stress of the pancreas in diabetes.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the amount of LPO product, MDA was higher in diabetic rats' pancreas as compared no non-diabetic rats indicating of high levels of oxidative stress due to intensified free-radical formation 53 . Our findings were in agreement with Kade et al 54 who reported that high amount of LPO product was observed in diabetic rats' pancreas. C. borivilianum root extract administration to diabetic rats lowered the LPO product, indicating that this plant extract could prevent elevation of oxidative stress of the pancreas in diabetes.…”
Section: Discussionsupporting
confidence: 94%
“…A lot of scientific research studies provide potential evidence about health benefits of polyphenol to humans. Particularly, gallic acid is reported to produce antioxidant effect by elevating the decreased levels of hepatic catalase enzyme and vitamin C in diabetic rats, and it also defend against damage produced by oxidative stress in hyperglycemic state [36,37]. Caffeic acid potentially reduces weight loss, plasma glucose, and triglycerides levels and increases insulin concentration in diabetic rats [38].…”
Section: Estimation Of Intracellular Ros and Measurement Ofmentioning
confidence: 99%
“…Intra-venous injection of 60mg/kg dose of streptozotocin in adult Wistar rats, makes pancreas swell and at last causes degeneration in Langerhans islet beta cells and induces experimental diabetes mellitus in 2-4 days [37]. Both alloxan and STZ have been extensively documented for the induction of diabetes via free radical generation and depletion of antioxidant defense system [38][39][40]. STZ has been reported to significantly decrease the activity of erythrocytes antioxidative enzymes catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) [38][39].…”
Section: Drug-induced Diabetic Mellitus and Their Mechanisms Of Actionmentioning
confidence: 99%
“…Both alloxan and STZ have been extensively documented for the induction of diabetes via free radical generation and depletion of antioxidant defense system [38][39][40]. STZ has been reported to significantly decrease the activity of erythrocytes antioxidative enzymes catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) [38][39]. Several drugs, with pharmacological properties including theophylline, aspirin, isoniazid and nalidixic acid can cause transient hyperglycaemia in over dosage, but only streptozotocin, alloxan and the rodenticide vacor are likely to cause permanent diabetes.…”
Section: Drug-induced Diabetic Mellitus and Their Mechanisms Of Actionmentioning
confidence: 99%